Szenci Molnár Albert hagyatéka - Ősz, Sándor Előd (Studia Litteraria, 2026)
No detailed inventory of Albert Szenci Molnár’s library has survived. The (at least partial) reconstruction of his legacy has been an important thread of Szenci-research for more than a century. Scholars have regularly reported their findings in this area at relevant academic forums. In the present study, we have attempted to summarize and compare these studies. At present, we know of a total of 39 volumes that were, for shorter or longer periods, in the possession of Albert Szenci Molnár. Of these, three are manuscripts and seventeen are printed volumes (containing altogether twenty-four printed works) that formed an organic part of his library. In addition, we know of nineteen volumes that he gave as gi³s to others, fifteen of which are his own writings.